Surface Dopants‐Induced Interfacial Bonding Greatly Enhances Active Phase‐Support Interaction of Sintering‐Resistant Catalyst for Automotive CO Oxidation. Issue 18 (18th August 2022) - Li, Mingxuan; Huang, Zhiwei; Wang, Lipeng; Guo, Sufeng; Fang, Jinxu; Liu, Yuchen; Chen, Junmou; Wu, Xiaomin; Shen, Huazhen; Zhao, Huawang; Jing, Guohua
Abstract: Supported nanoparticle catalysts are widely used to remove CO pollution in automobile emission control. During vehicle use, catalysts need to experience high‐temperature environments, leading to sintering of active phase and loss of activity. Synthesizing cost‐effective catalysts with simultaneously high catalytic activity and sintering resistance is of great importance but remains challenging. In this study, we show that Cu phase supported on commercial antimony‐doped tin oxide (ATO) is relatively resistant to sintering and can operate at temperatures below 200 °C without any performance degradation after high temperature aging. Specifically, T50 (the temperature of 50 % conversion) of CO conversion over the Cu/ATO sample is maintained at 148 °C before and after high‐temperature aging treatment at 800 °C. The strong active phase‐support interactions could be used to stabilize Cu active phase by taking advantage of extra interfacial bonding stability between Cu islands and surface antimony dopants in ATO, and finally tune activity and stability of the catalysts. The Cu‐on‐ATO ensemble shows excellent resistance against sintering, with conversion efficiency remaining nearly unchanged upon high‐temperature aging at 800 °C for 2 to 10 h. In contrast, strong sintering resistance characteristic of catalysts cannot be attained by supporting Cu on undoped tin oxide (SnO2 ) or conventional Al2 O3 due to absence of specific anchoring sites on the support oxide surfaces. Our findings open up the path in heterogeneous catalysis for the design of active and sintering‐resistant catalysts utilizing surface engineering strategies. Abstract : Automotive Emission Abatement : Active phases of Cu‐loaded antimony‐doped tin oxide catalyst exhibiting excellent thermal stability are prepared. Based on surface science studies and various controlled experiments, we reveal that the high stability of ATO‐supported Cu catalyst is due to the extra bonding between Cu active phase and surface Sb dopants. In contrast, the strong sintering resistance characteristic of catalysts that could not be attained by supporting Cu on conventional Al2 O3 .